A mechanical DCCB with re-closure capability and its performance in MMC based DC grid. (October 2020) - Ni, Binye; Xiang, Wang; Zhou, Meng; Lu, Xiaojun; Zuo, Wenping; Yao, Wei; Wen, Jinyu
Highlights: The DCCB is able to automatically re-close after DC faults with minimum cost. The operating principle and the dynamics during DCCB operation are analysed. The general parameters design method of the proposed mechanical DCCB is disclosed. The feasibility of the mechanical DCCB is verified in a four-terminal meshed DC grid. Abstract: For the modular multilevel converter (MMC) based DC grids using overhead line transmission, to restore the power transmission quickly, the DC circuit breakers (DCCB) are required to be able to re-close after DC line faults. To meet this requirement, an improved mechanical DCCB topology with re-closure capability is proposed in this paper. It consists of a pre-charged capacitor, an auxiliary capacitor, an oscillation inductor, and anti-parallel thyristors. Firstly, the topology and operating principle of the mechanical DCCB are presented in detail. Then, the general sizing methods associated with the impact of parameters on interruption capability are disclosed. The feasibility of the proposed mechanical DCCB is validated in a stiff DC system. Finally, the transient performance of the DC grid embedding the proposed mechanical DCCBs is investigated under various operating scenarios. The results verify the DC fault interruption and fast automatic re-closure capabilities of the proposed DCCB. It is shown that the mechanical DCCBs can be well applied to the overhead MMC based HVDC grids systems.